Low transferrin and high ferritin concentrations are associated with worse outcome in acute liver failure. (12th February 2017) - Anastasiou, Olympia E.; Kälsch, Julia; Hakmouni, Mahdi; Kucukoglu, Ozlem; Heider, Dominik; Korth, Johannes; Manka, Paul; Sowa, Jan‐Peter; Bechmann, Lars; Saner, Fuat H.; Paul, Andreas; Gerken, Guido; et al.
Abstract: Background & Aims: Serum ferritin and transferrin have been identified as prognostic markers in patients with chronic diseases. In this study, we investigated if these parameters can predict outcome in patients with acute liver failure. Methods: A total of 102 consecutive patients with acute liver failure were retrospectively analysed. The patients were grouped by outcome: spontaneous recovery vs liver transplantation and/or death or survival vs death. Routine laboratory parameters, transferrin and ferritin concentrations in serum, and anthropomorphic data collected on admission were analysed. Results: Non‐spontaneously recovering patients had higher ferritin (12 252±25 791 vs 4434.4±9027.2 μg/L; P <.05) and lower transferrin levels (140.4±66.7 vs 206.9±65.8 mg/dL; P <.05) than spontaneously recovering patients. Similarly non‐survivors exhibited higher serum ferritin and lower transferrin than non‐transplanted survivors. Patients with severe hepatic inflammation (A3) had higher ferritin levels compared to patients with mild‐moderate inflammation (A1‐2) (5280±5094 vs 2361±2737 μg/L; P =.025). ROC analysis of single parameters was performed in non‐transplanted patients, resulting in an area under the curve, sensitivity and specificity of 0.812%, 83.3%, and 77.1% for age, 0.871%, 84.1% and 75% for transferrin and 0.802%, 91.7% and 62.9% for ferritin. A model incorporating age, MELD and transferrin had the best predictive value with an area under the curve of 0.947, a sensitivity of 100% and corresponding specificity of 77.8%. Conclusions: High ferritin and low transferrin levels are associated with worse outcome in patients with acute liver failure. A model incorporating age, MELD score and transferrin outperformed MELD score for 90‐day overall survival of non‐transplanted patients.